INTERPERSONAL METAFUNCTION IN INDONESIA’S INDEPENDENCE DAY SLOGANS (2015–2025) - Syafitri, Siska Eka; Sanjaya, Muhammad Arif; Pratiwy, Devi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study analyzes Indonesia’s Independence Day slogans from 2015 to 2025 through Halliday’s Systemic Functional Linguistics, focusing on Interpersonal Metafunction. As annual commemorative texts, these slogans function not only as symbolic expressions of independence but also as strategic discourses that negotiate power, construct solidarity, and reinforce national identity. Employing qualitative discourse analysis, the research investigates mood, modality, pronoun usage, evaluative lexis, and the interplay of explicit and implicit meanings. The findings indicate that declarative and imperative moods position citizens within relationships of inclusivity and responsibility, while modality expresses urgency and commitment. Evaluative vocabulary conveys optimism and resilience, with explicit meanings emphasizing productivity, recovery, and progress, and implicit meanings connecting contemporary challenges to historical struggles and the long-term vision of Indonesia Emas 2045. Overall, Independence Day slogans function as condensed ideological texts that bridge past sacrifices with future aspirations, illustrating the discursive power of language in shaping nationalism and providing practical insights for developing effective national slogans.